The First Results of Application of Novel Biopolymers in Surgery and Medicine and their Potentials - Yuri S. Vinnik; Nadezhda M. Markelova; Sergey V. Miller; Ekaterina S. Vasilyenya; Elena S. Cherepanova; Andrey V. Yakovlev; Elena V. Repina; Andrey A. Shageev; Ekaterina I. Shishatskaya (Журнал Сибирского федерального университета: Серия Биология, 2012)
The paper reports analysis of results of the first limited clinical trials of high technology medical devices prepared using polyhydroxyalkanoates (PHAs) – degradable microbial biopolymers: PHA coated mesh stents for surgical repair of inguinal hernia, endobiliary stents for treatment of the patients with obstructive jaundice caused by extrahepatic biliary obstruction due to different reasons, and biodegradable monofilament sutures for closing operative wounds on the abdominal wall. The devices were compared with their commercial Russian and foreign analogs widely used clinically. The choice of the device influenced the incidence of early and delayed postsurgical complications and laboratory and clinical parameters. The study proves the suitability of PHA-based devices for reconstructive surgery.